Diagnostic performance of various liquid biopsy methods in detecting colorectal cancer: A meta‐analysis. (6th July 2020) - Zhu, Yuzhou; Yang, Tinghan; Wu, Qingbin; Yang, Xuyang; Hao, Jianqi; Deng, Xiangbing; Yang, Shuo; Gu, Chaoyang; Wang, Ziqiang
Abstract: Liquid biopsy is a promising method in detecting colorectal cancer (CRC). However, previous meta‐analyses only focused on the diagnostic performance of cell‐free DNA (cfDNA). Therefore, we firstly evaluated the overall performance of all liquid biopsy methods. The pooled sensitivities, specificities, diagnostic odds ratios, and area under curve (AUC) of summary receiver operating characteristic curve for all liquid biopsy methods, exosomes, circulating tumor cells (CTCs), and cfDNA were calculated, respectively. A total of 62 articles involving 18 739 individuals were included. Fifty‐one articles were about cfDNA, five articles were about CTCs, and six articles were about exosomes. The overall performance of all liquid biopsy methods had a pooled sensitivity, specificity, and AUC of 0.77 (95% confidence interval [CI] 0.76‐0.78), 0.89 (95% CI 0.88‐0.90), and 0.9004, respectively. The sensitivities were 0.82 (95% CI 0.79‐0.85), 0.76 (95% CI 0.72‐0.80), and 0.76 (95% CI 0.75‐0.77) for CTCs, exosomes, and cfDNA, respectively. The specificities were 0.97 (95% CI95% CI 0.95‐0.99), 0.92 (95% CI 0.89‐0.94), and 0.88 (95% CI 0.87‐0.89) for CTCs, exosomes, and cfDNA, respectively. The AUC were 0.9772, 0.9037, and 0.8963 for CTCs, exosomes, and cfDNA, respectively. The overall performance of all liquid biopsy methods had great diagnostic value in detecting CRC, regardless of subtypes. Among all liquid biopsy methods, CTCs showed the best diagnostic performance. Abstract : The area under curve was 0.9772, 0.9037, 0.8963, and 0.9004 for circulating tumor cells (CTCs), exosomes, cell‐free DNA, and overall performance of all liquid biopsy methods in detecting colorectal cancer, respectively. The liquid biopsy had great diagnostic value in detecting CRC, regardless of subtypes. Among all liquid biopsy methods, CTCs showed the best diagnostic performance.